9a2b2 – 25
= (3ab)2 – (5)2
By using the formula a2 – b2 = (a + b)(a – b)
9a2b2 – 25 = (3ab)2 – (5)2
= (3ab + 5)(3ab – 5)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
Fill in the blankNCERT - Mathematics Exemplar